Origin - Brown, Dan, 1964- (Robert Langdon series, 2017)
Robert Langdon, Harvard professor of symbology and religious iconology, arrives at the Guggenheim Museum Bilbao to attend the unveiling of a discovery that "will change the face of science forever". The evening's host is his friend and former student, Edmond Kirsch, a forty-year-old tech magnate whose dazzling inventions and audacious predictions have made him a controversial figure around the world. This evening is to be no exception: he claims he will reveal an astonishing scientific breakthrough that will answer two of the fundamental questions of human existence. But the meticulously orchestrated evening suddenly erupts into chaos. Langdon is forced into a desperate bid to escape Bilbao. With him is Ambra Vidal, the elegant museum director who worked with Kirsch to stage the provocative event. Together they flee to Barcelona on a perilous quest to locate a cryptic password that will unlock Kirsch's secret. Navigating the dark corridors of hidden history and extreme religion, Langdon and Vidal must evade a tormented enemy whose all-knowing power seems to emanate from Spain's Royal Palace itself.